Electrically driven cation exchange for in situ fabrication of individual nanostructures - Qiubo Zhang (Nature Portfolio, 2017)
Cation exchange, traditionally driven by ion solvation or thermal activation, is a robust approach for preparing heterogeneous nanostructures but lacks selectivity for preparation of individual nanocrystals. Here, the authors report an electrically driven cation exchange reaction that enables them to fabricate individual nanocrystals with high selectivity.